The effect of landscape composition and configuration on the spatial distribution of temperate demersal fish - Moore, Cordelia; Van Niel, K.; Harvey, Euan (Blackwell Publishing, 2011)
In contrast to the terrestrial environment, where the use of landscape analyses has been clearly demonstrated, the influence of landscape composition and configuration on the abundance and spatial distribution of marine organisms remains poorly understood. Development of this area of marine research has been limited by the lack of accurate benthic habitat maps, particularly for marine environments deeper than can be penetrated by optical remote sensing (<10 m). However, the recent availability of detailed (1:25 000) and accurate habitat maps derived from hydroacoustic surveys of deeper marine waters has redressed this situation. The aim of this research was to establish the strength and significance of derived landscape composition and configuration indices on the demersal fish assemblage structure and spatial distribution. A combination of depth and 6 landscape measures were found to explain 34.8% of the variation in the fish assemblage. Depth contributed the highest percentage of the variance explained, accounting for 23.7%. Distance to reef was the most important landscape index explaining 7.1% of the variability, followed by total length of edge environment (the interface between different benthic substrates) explaining 1.5%. Species responsible for driving the structure of the fish assemblage were also examined and found to respond not only to the proximity of reef but also to the configuration of the reef. For example, Parika scaber and Pseudolabrus psittaculus characterised more heterogeneous landscapes offering clusters of small interconnected patches of reef with a lot of edge environment, whilst juvenile Trachyurus novaezelandiae and Platycephalus caeruleopunctatus preferred more homogeneous landscapes offering little reef or edge environment. This research demonstrated that a broad scale landscape analysis, employing indices of landscape composition and configuration, is important for understanding demersal fish assemblage structure and spatial distribution.